PROMOSI CAFE DAMAR SHAKER DALAM MEDIA DESAIN WEB - Ririn Emilia; Ady Rosa; Hendra Afriwan (DEKAVE : Jurnal Desain Komunikasi Visual, 2012)
Absract   The purpose of this research is to design the web promotion  media for Damar Shaker Cafe. It is designed to built up to growth of this cafe with steak and shake as the main menu. The data is got and analyzed by using SWOT method. This method is aimed to explain the strenght, the weakness, the probability, and treath of web media as a promotion vehicle. The design of this media display the following pages: home, profile, menu, gallery, and contact. This media planning is proposed to promote dammar shaker café widely and to elarge the target audience. In addition this is hoped to guide large number of custumer who do not know yet this café to be familiar with is. As a result, instead of being a place to eat, this café can be a recommedended place to hang out with friends. This can be easily reach by such of this media promotion. Kata kunci: web, cafe, damar shaker, promosi